Do the Numbers Add Up to Different Views? Perceptions of Ethical Faculty Behavior Among Faculty in Quantitative Versus Qualitative Disciplines - Kidwell, Linda A. (Journal of business ethics, 2008)
Faculty across a wide range of academic disciplines at 89 AASCB-accredited U.S. business schools were surveyed regarding their perceptions of the ethical nature of faculty behaviors related to undergraduate course content, student evaluation, educational environment, research issues, financial and material transactions, and social and sexual relationships. We analyzed responses based on whether instruction in the academic discipline focused mainly on quantitative topics or largely on qualitative issues. Faculty who represented quantitative disciplines such as accounting and finance (n = 383) were more likely to view behaviors such as selling complimentary textbooks and grading on a strict curve as more ethical than faculty representing more qualitative disciplines such as management and marketing (n = 447). In contrast, faculty in quantitative disciplines were more likely to view behaviors such as showing controversial media and bringing up sexual or racial charged matters as less ethical than their counterparts. Whereas these differences may be attributed to the respondents’ academic backgrounds, the large level of agreement on ethical behaviors raises questions about the growing influence of business disciplines that operate within more unified research and teaching paradigms.